2007
DOI: 10.1111/j.1440-1746.2006.04680.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors of celiac disease: Cytotoxicity of hulled wheat species Triticum monococcum, T. turgidum ssp. dicoccum and T. aestivum ssp. spelta

Abstract: The results have shown a constant and significant toxic effect of spelt wheat which is not shared by the two other ancient cereals. Future studies on celiac intestinal organ cultures are needed to increase the prospects of breeding programs aimed at developing wheat cultivars potentially tolerated by most celiac patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 45 publications
(86 reference statements)
1
39
0
3
Order By: Relevance
“…Consistent with previous results [28][29], statistically significant TEER decrement was observed only after treatment for 4 h with PTG compared with treatment with medium alone (p < 0.01; Figure 1C). PT-digests from the two oat varieties were not able to induce TEER decrement ( Figure 1C), indicating that, differently from gliadin, the oats did not alter permeability.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Consistent with previous results [28][29], statistically significant TEER decrement was observed only after treatment for 4 h with PTG compared with treatment with medium alone (p < 0.01; Figure 1C). PT-digests from the two oat varieties were not able to induce TEER decrement ( Figure 1C), indicating that, differently from gliadin, the oats did not alter permeability.…”
Section: Resultssupporting
confidence: 94%
“…The measurement of TEER represents a good method to assay the integrity of epithelial barrier and of the polarized CaCo-2 cell monolayer in response to several insults. It was shown that gliadin induces TEER decrement after 4 h of treatment in CaCo-2 cell monolayers [28][29].…”
Section: Resultsmentioning
confidence: 99%
“…These results cast doubt on the claims of the manufacturer of the spelt cakes (sample 7) that 'in laboratory experiments no gluten was isolated from the spelt cakes' (Figure 1b), and that the spelt cakes 'may be suitable for individuals who have celiac disease'. Evidence strongly suggests that spelt exerts toxic effects similar to that of common wheat in celiac disease sufferers (Vincentini et al, 2007). The buckwheat flour (sample 8) tested negative for wheat (Table 1), an anticipated result since buckwheat is not considered to be taxonomically closely related to wheat (Anand, Piris, & Truelove, 1978;FDA, 2007;Kasarda, 2001) and therefore was not expected to be recognised by wheat-specific PCR primers.…”
Section: Resultsmentioning
confidence: 95%
“…Earlier studies (De Vincenzi et al 1996c;Molberg et al 2005;Vincentini et al 2007) showed diploid and tetraploid hulled wheat species T. monococcum and T. turgidum ssp. dicoccum to be poor in or devoid of noxious prolamins.…”
mentioning
confidence: 99%